Using life and death education to guide the teaching and research of mindfulness - Phan, Huy P.; Ngu, Bing Hiong; Chen, Si-Chi; Hsu, Chao-Sheng (Frontiers in Public Health, 2025)
Our teaching and research undertakings, facilitated by extensive international collaboration and networking, have led us to recently proposed an alternative conceptualization of mindfulness. For example, mindfulness has been predominantly interpreted through a psychological lens, often defined as an individual's capacity to be non-judgmental in the present moment. This perspective, we acknowledge, is limited as it fails to acknowledge and/or take into account the broader philosophical and spiritual dimensions of mindfulness. Our reconceptualization largely coincides with the principles of life and death education teaching, which delve into the humanistic nature of life. Life and death education encourages introspection into humanistic pursuits, such as the aspiration to achieve altruistic life ideals (e.g., a teenager's wish to help others). Such personal practices, we contend, may resonate with the deeper philosophical and spiritual teachings of mindfulness, which emphasize the importance of kindness, generosity, compassion, and similar values. Our conceptualization, as discussed in the present theoretical-conceptual article, proposes a reciprocal relationship between mindfulness and life and death education. We argue that life and death education may provide theoretical grounding to complement the teaching of mindfulness and, likewise, the nature of mindfulness may facilitate a deeper engagement with the principles taught in life and death education. Furthermore, in its current stage of development, our theoretical-conceptual premise remains formative, grounded primarily in philosophical analysis and preliminary integrative teaching practices. While conceptually promising, we recognize the present limitations in empirical validation. Accordingly, this article is intended to serve as a foundational platform to stimulate scholarly discourse and guide future lines of inquiry, including empirical examination and curriculum development. We posit that the integration of mindfulness with life and death education holds considerable potential—not only for advancing academic scholarship but also for fostering individual wellbeing, spiritual insight, and the cultivation of humanistic life ideals.